Recovery of the patient with lumbar disc hernia by kinetic means - Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
The present work aims to demonstrate the importance of physical therapy in a lumbar disc herniation rehabilitation program. Due to its frequency and the problems it creates, related to the inability to work, the condition is starting to become a social disease. This is becoming more and more common in society, making it impossible for the subject to perform various activities from an early age.[5,7,12] The aim pursued in this work is to recover the patient with lumbar disc herniation. The general goal of rehabilitation is to help the patient recover as quickly as possible, to prevent physical discomfort and, in particular, to stop the worsening of the disease. Following the performance of the three initial tests and the three final tests by the patient, we were able to collect the results presented in the paper and draw up the final conclusions of the study.